2016
DOI: 10.1128/jvi.01263-15
|View full text |Cite
|
Sign up to set email alerts
|

Viral DNA-Dependent Induction of Innate Immune Response to Hepatitis B Virus in Immortalized Mouse Hepatocytes

Abstract: Hepatitis B virus (HBV) infects hundreds of millions of people worldwide and causes acute and chronic hepatitis, cirrhosis, and hepatocellular carcinoma. HBV is an enveloped virus with a relaxed circular (RC) DNA genome. In the nuclei of infected human hepatocytes, conversion of RC DNA from the incoming virion or cytoplasmic mature nucleocapsid (NC) to the covalently closed circular (CCC) DNA, which serves as the template for producing all viral transcripts, is essential to establish and sustain viral replicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 65 publications
0
32
1
2
Order By: Relevance
“…A recent study has proposed that HBV triggers antiviral innate immunity through retinoic acid-inducible gene (RIG-I) activation from RNA produced from HBV's DNA genome (30). In addition, other recent studies have demonstrated a role for the STING-TBK1-IRF3 in detection of HBV (35,36). Our studies were unable to substantiate a role for the STING pathway in early HBV responses.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…A recent study has proposed that HBV triggers antiviral innate immunity through retinoic acid-inducible gene (RIG-I) activation from RNA produced from HBV's DNA genome (30). In addition, other recent studies have demonstrated a role for the STING-TBK1-IRF3 in detection of HBV (35,36). Our studies were unable to substantiate a role for the STING pathway in early HBV responses.…”
Section: Discussioncontrasting
confidence: 91%
“…To further investigate the recognition of foreign DNA in hepatocytes, we also examined the stimulator of IFN genes (STING) pathway that has been shown to be important for DNA responses and innate responses to HBV (17,35,36). Interestingly, knockdown of STING and the associated molecule cGAS and downstream proteins TBK1 and IRF3 had dramatic effects on gene induction by ISD, demonstrating almost complete inhibition (Fig.…”
Section: Role Of Known Dna-sensing Pathways In Innate Immune Responsementioning
confidence: 99%
“…Consistently, Cui et al . showed that HBV DNA could be detected by DNA sensors, specifically the cGAS/STING signaling pathway, in an immortalized mouse hepatocyte cell line [19]. On the other hand, HBV was shown to counteract the MITA/STING-mediated antiviral responses by disrupting K63-linked ubiquitination of MITA/STING [24].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is possible that HBV is detected by the innate immune system, while the virus can actively suppress or evade the early antiviral response. Indeed, recent studies have shown that the pgRNA (pregenomic RNA) of HBV and the cytoplasmic exposed HBV rcDNA (relaxed circular DNA), a result of nucleocapsid destabilization, could be detected by RIG-I and MITA/STING, respectively [19, 20]. The activation of different innate immune signaling pathways may induce type III IFN response and inhibit HBV replication [20].…”
Section: Introductionmentioning
confidence: 99%
“…Cui et al. failed to detect the induction of IFN‐α, IFN‐ÎČ, IFN‐λ, TNF‐α and IL‐6 when viral gene expression and replication were clearly being suppressed, and Liu et al. recently revealed that rather than being silent, HBV may be efficient in inducing anti‐/pro‐inflammatory cytokines, but less potent to activate IFN response in patients .…”
Section: Discussionmentioning
confidence: 99%